Hungarian Refugees in the United Kingdom in the Context of the Domestic Policy (1956–1957) - Kopyś, Tadeusz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
After the suppression of the 1956 uprising in Hungary, a large group of political refugees, most of them young and often highly skilled professionals, left for the West. Most of the refugees fled to Austria. Austria immediately called on countries to help both financially and physically by resettling the refugees. Most of the refugees were very quickly resettled in other countries. These facts stand in stark contrast to contemporary resettlement practice, which is characterized by a shortage of resettlement sites and a small number of resettlement countries. The scarcity of jobs and the peculiarities of the migration policies of some countries (e.g., the United Kingdom) meant that some refugees could not find a long-term place in European countries and therefore sought refuge overseas. In 1956 and 1957, Canada took in more than 37,500 Hungarian refugees. The United States was also a more common c Hungarian Refugees in the United Kingdom in the Context hoice for refugees than the United Kingdom, for example. Po stłumieniu powstania na Węgrzech w 1956 r. na Zachód wyjechała liczna grupa uchodźców politycznych, w większości młodych i często wysoko wykwalifikowanych fachowców. Większość uchodźców uciekła do Austrii. Austria natychmiast wezwała państwa do pomocy zarówno finansowej, jak i fizycznej poprzez przesiedlenie uchodźców. Większość uchodźców została bardzo szybko przesiedlona do innych krajów. Fakty te stoją w jaskrawym kontraście ze współczesną praktyką przesiedleńczą, która charakteryzuje się niedoborem miejsc przesiedlenia i niewielką liczbą państw przesiedleńczych. Niedobory miejsc pracy oraz specyfika polityki migracyjnej niektórych krajów (np. Wielkiej Brytanii) spowodowały, że część uchodźców nie znalazła na dłużej miejsca w krajach europejskich i dlatego szukali schronienia za oceanem. W latach 1956 i 1957 Kanada przyjęła ponad 37 500 węgierskich uchodźców. Stany Zjednoczone były też częściej wybierane przez uchodźców niż np. Wielka Brytania.
Węgierscy uchodźcy w Wielkiej Brytanii w kontekście polityki krajowej (1956–1957)
Keywords: 1956 revolution; Hungary; refugees; Great Britain; migration policy; rewolucja 1956; Węgry; uchodźcy; Wielka Brytania; polityk migracyjna